Brevinin-GR23 from frog Hylarana guentheri with antimicrobial and antibiofilm activities against Staphylococcus aureus. Issue 1 (2nd January 2020) - Zhong, Hengren; Xie, Zhipeng; Zhang, Shuxia; Wei, Hanqi; Song, Yanting; Zhang, Yingxia; Wang, Manchuriga
ABSTRACT: Brevinin-GR23 (B-GR23) was a brevinin-2 like antimicrobial peptide, which had antimicrobial activity against Staphylococcus aureus with minimum inhibitory concentration (MIC) of 16 μM. B-GR23 increased the bacterial membrane permeation, leading to the damage of membrane integrity and the leakage of genomic DNA, then causing the cell death. The peptide nearly inhibited all plantonic bacteria to start the initial attachment of biofilm at the concentration of 1 × MIC. Whereas the disruption rates on immature and mature biofilm decreased from 60% to 20%. B-GR23 reduced the production of extracellular polysaccharides (EPS) in the planktonic growth of S. aureus, which is a crucial structure of biofilm formation. B-GR23 with the concentration of ½ × MIC inhibited 50% water-soluble EPS, and 48% water-insoluble EPS, which contributed to the antibiofilm activity. B-GR23 had no significant toxicity to human blood cells under-tested concentration (200 μM), making it a potential template for designing antimicrobial peptides. Graphical abstract: : Brevinin-GR23, a stable antimicrobial and antibiofilm peptide against Staphylococcus aureus